Assessment Of The Knowledge About Exercise Induced Asthma Among Middle School Physical Education Teachers In Chlef State, Algeria. - Oudjedi Adda,; Said Aissa Khelifa ., (sports creativity, 2025)
Objective: To assess the level of knowledge regarding exercise induced asthma and its management among physical education teachers working in middle schools in Chlef state, Algeria. Methods: A descriptive cross-sectional study design was used to examine physical education teachers recruited from 20 randomly selected middle schools between January and February 2019. The study sample consisted of 45 teachers. A face-validated questionnaire was used to collect data from the participants. The collected data were reviewed and statistically analyzed by using SPSS. Results: Overall, 80٪ of teachers had experience with teaching pupils with asthma in their physical education classes. Only15٪ reported knowing Exercise as an asthma trigger, and 87, 5٪ of teachers didn’t have competencies for dealing with asthma attacks. In addition, 95٪ reported the unavailability of asthma medications in schools, which reflected an absence of an asthma action plan in schools. Conclusion: The results suggest a knowledge deficit among this sample of teachers , and they are not adequately prepared to teach pupils with asthma due several barriers like lack of communication with parents, medications availability, asthma training program for teachers and lack of an asthma action plan ( asthma management), as well as developed countries.